Analisis Pengaruh Faktor Produk, Merek, dan Channel terhadap Keputusan Pembelian Konsumen Brand Mixue - Yurinonica, Aveidel Arven; Yusrin, Nur Amalyna (Reviu Akuntansi, Manajemen, dan Bisnis, 2024)
Purpose: One of the developments in the F&B (Food and Beverage) industry in the world in the form of dessert which is currently increasing is Mixue ice cream & tea which comes from a franchise company from China founded in 1997 which has achieved success in the ice cream industry with more than 10,000 outlets both in and outside China. This The purpose of this research is useful in further researching product, brand and channel factors that can influence purchasing decisions for the Mixue brand. It is hoped that the theoretical benefits will be able to add to case studies regarding product, brand and channel factors. Practical benefits, research can provide input to the Mixue brand or other ice cream outlet brands to develop marketing strategies so as to increase the potential for purchase conversions Research methodology: The research method used was quantitative, involving 93 respondents from the Indonesian area. Results: The result of the regression analysis shows that brand and channel have a significant positive influence on purchasing decisions, while product is not significant. The strategic implication of these findings can help Mixue and similar industries optimize marketing strategies and increase consumer purchasing potential. Limitations: 1. In the research, the three variables that have a significant positive relationship and are accepted are only brand and channel, while products have negative value. 2. In this research, there is no intermediary or mediating factor between variable x and variable y. Contribution: The author advises that because competition is getting tougher with the many competitors of other F&B stores such as Momoyo, Wedrink and Ai-Cha, therefore Mixue must be able to meet the needs of its consumers, such as improving its products by increasing the variety of menus that consumers want. The Mixue channel is expected to continue to improve. up to date and make the content as interesting as possible on social media so that people don't miss out on finding out information about Mixue itself as well as increasing the number of branches or outlets in strategic positions so they are easy to reach.